Population‐based cohort study of surgical myotomy and pneumatic dilatation as primary interventions for oesophageal achalasia. Issue 8 (30th March 2018) - Markar, S. R.; Mackenzie, H.; Askari, A.; Faiz, O.; Hoare, J.; Zaninotto, G.; Hanna, G. B.
Abstract : Background: The aim of this national population‐based cohort study was to compare rates of reintervention after surgical myotomy versus sequential pneumatic dilatation for the primary management of oesophageal achalasia. Methods: Patients with oesophageal achalasia diagnosed between 2002 and 2012, and without an intervention in the preceding 5 years were identified from the Hospital Episode Statistics database. Patients were divided into two groups based on the primary treatment, and propensity score matching was used to compensate for differences in baseline characteristics. Results: Some 14 705 patients were diagnosed with oesophageal achalasia, of whom 7487 (50·9 per cent) received interventional treatment: 1742 (23·3 per cent) surgical myotomy, 4534 (60·6 per cent) pneumatic dilatation and 1211 (16·2 per cent) endoscopic botulinum toxin injection. As age increased, the proportion of patients receiving myotomy decreased and the proportion undergoing dilatation increased. Patients who underwent surgical myotomy were younger (mean age 44·8 years versus 58·5 years among those who had pneumatic dilatation; P  < 0·001), a greater proportion had a Charlson co‐morbidity index score of 0 (90·1 versus 87·7 per cent; P  = 0·003) and they were more commonly men (55·6 versus 51·8 per cent; P  = 0·020). Following propensity score matching, the safety of the two initial treatment approaches was equivalent, with no difference in incidence of oesophageal perforation (1·3 and 1·4 per cent after myotomy and dilatation respectively; P  = 0·750). However, dilatation was associated with increased need for reintervention (59·6 versus 13·8 per cent; P  < 0·001) and frequency of reinterventions (mean 0·34 versus 0·06 per year; P  < 0·001). Conclusion: Surgical myotomy was associated with a lower rate of reintervention and could be offered as primary treatment in patients with oesophageal achalasia who are fit for surgery. For those unfit for surgery, pneumatic dilatation may provide symptomatic relief with approximately 60 per cent of patients requiring reintervention. Abstract : Fewer reinterventions after surgical myotomy